Impaired Color Recognition in HCN1 Epilepsy: A Single Case Report - Mckenzie, Chaseley E.; Ho, Chen-Jui; Forster, Ian C.; Soh, Ming S.; Phillips, A. Marie; Chang, Ying-Chao; Scheffer, Ingrid E.; Reid, Christopher A.; Tsai, Meng-Han (Frontiers in Neurology, 2022)
Variants in HCN1 are associated with a range of epilepsy syndromes including developmental and epileptic encephalopathies. Here we describe a novel de novo HCN1 variant, E246A, in a child with epilepsy and mild developmental delay. The child had difficulty in discriminating between colours implicating a visual deficit. This interesting observation may relate to the high expression of HCN1 channels in rod and cone photoreceptors where they play an integral role in shaping the light response. Functional analysis of the HCN1 E246A variant revealed a right shift in the voltage dependence of activation and slowing of the rates of activation and deactivation. The changes in the biophysical properties are consistent with a gain-of-function further supporting the role of HCN1 E246A in disease causation. This case suggests that visual function, including colour discrimination, should be carefully monitored in patients with diseases due to HCN1 pathogenic variants.